Taken [videorecording (DVD)] - Besson, Luc; Kamen, Robert Mark; Neeson, Liam; Grace, Maggie, 1983-; Orser, Leland; Gries, Jon, 1957-; Warshofsky, David; Cassidy, Katie, 1986-; Valance, Holly, 1983-; Janssen, Famke, 1964-; Abramowicz, Michel; Méchaly, Nathaniel, 1972- (20th Century Fox Home Entertainment, 2009)
Kim is seventeen years-old and the pride and joy of her father, the ex-CIA agent Bryan Mills. Kim convinces the reluctant Bryan to sign an authorization form so she can travel to Paris with her friend Amanda. When they arrive, they share a cab with a stranger named Peter. Amanda tells him that they are alone in Paris. While Bryan is on the phone with Kim, Albanian gang members break into the apartment where the girls are staying. Bryan has Kim give him a detailed description of what she sees and hears. He tells her she is about to be kidnapped. Bryan promises Kim that he will come and get her. He immediately travels to Paris to find Kim and Amanda. He has four days to find her and he uses his special skills and contacts to get her back and seek his revenge.